The Use of E-Gov Through the Village Financial Information System (Siskeudes) and the Village Information System (SID) as a Means of Transparency of Financial Planning and Management in Sidoarjo Regency - Rini Nofita; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2022)
This research is to find out how the use of E-Gov in planning through the village financial information system (Siskeudes) and the village information system (SID) in the Tanggulangin district, To find out how the use of E-Gov in financial management through the village financial information system (Siskeudes) and the Village information (SID) in the Tanggulangin district and to find out the level of financial transparency by using E-Gov through the village financial information system (Siskeudes) and village information system (SID) in the Tanggulangin district. In this study, researchers used qualitative methods. The informants in this study were the sub-district head, the head of the sub-district administration and the village treasurer. Data collection techniques used are interviews, observation and documentation. In this study, the triangulation used is source triangulation. Source triangulation means comparing by re-checking the degree of trust of an informant obtained through different sources. The village financial system (Siskeudes) and the village information system (SID) are applications of e-gov or e-government in the field of financial planning and management. The village financial management process is the entire activity that includes planning, budgeting, administration, accountability and supervision of village finances. All of these processes were initially carried out manually until the central government required the use of the village financial system (Siskeudes) and the village information system (SID). With these two systems that can be accessed online, village financial planning and management can be carried out better, because the financial management process becomes more timely, accurate and has a high level of transparency. The two systems (Siskeudes and SID) play an important role in financial management. The village financial information system (Siskeudes) is the center or heart of village financial management, while SID is a means for financial transparency to the community.